The effect of pectins and xanthan gum on physicochemical properties of egg white protein foams. (January 2015) - Ptaszek, Paweł; Kabziński, Maciej; Kruk, Joanna; Kaczmarczyk, Kacper; Żmudziński, Daniel; Liszka-Skoczylas, Marta; Mickowska, Barbara; Łukasiewicz, Marcin; Banaś, Joanna
Highlights: Sauter diameter and the PDI of the bubble sizes are dependent on the methylation degree. The Kolmogorov–Smirnov test is an effective tool to analysis population gas bubbles in foam. The log-normal distribution provided the best description of the bubbles distributions. Abstract: The study analyzed the influence of the degree of apple pectin methylation and the concentration of xanthan gum on physicochemical properties of fresh wet egg white protein based foams. Molecular characterization of applied hydrocolloids was performed and amino acid composition of proteins was established. First, essential physicochemical properties of the starting solutions, i.e. density, surface tension and hydrophobicity, were analyzed, and electrophoretic analysis of the solutions was carried out. Density and content of the gaseous phase in the continuous phase were determined. The image analysis allowed assessment of the size distributions of gas bubbles and, subsequently, cross compliance of the population of obtained bubbles was performed using the Kolmogorov–Smirnov test. Next, using the maximum likelihood method, three distributions, i.e. Weibull, log-normal and gamma distributions, were matched to one another. The results showed that the log-normal distribution provided the best description of the bubble distribution.